Nonsplit Graphs with Split Maximal Induced Subgraphs - S Monikandan; V Manikandan (IndoMS, 2023)
A split graph is a graph in which the vertices can be partitioned into an independent set and a clique. A graph is split if and only if it has no induced subgraph isomorphic to C5, C4 or 2K2, which is a well-known characterization for split graph. A property of a graph G is recognizable if it can be recognized from the collection of all maximal proper induced subgraphs of G. We show that any nonsplit graph can have at most five split maximal induced subgraphs. Also we list out all C5-free nonsplit graphs having split maximal induced subgraphs, which is the main and, in fact, tedious result of this paper